Penguatan Kemampuan Speaking Bahasa Inggris pada Lansia melalui Pendekatan Fun learning di Sekolah Lansia Cahaya Kartini - Sri Suci Suryawati; Agus Hidayat; Meisuri; Septa Aryanika; Irawansyah; M.Fikri Nugraha Kholid (WISE Pendidikan Indonesia, 2026)
This community service program was motivated by the need to provide English language learning that is inclusive, enjoyable, and aligned with the characteristics of elderly learners. The program aimed to strengthen the English speaking skills of elderly participants through a fun learning approach at Sekolah Lansia Cahaya Kartini. It was conducted on February 19, 2026, by a team of lecturers from the English Education Study Program, Faculty of Tarbiyah and Teacher Training, UIN Raden Intan Lampung. The program employed a Participatory Action Research (PAR) design comprising four stages: planning, action, observation, and reflection. The learning materials focused on basic communication skills, including greetings, self-introduction, simple vocabulary, pronunciation, and daily conversations. The fun learning strategy was implemented through ice-breaking activities, language games, singing, role play, vocabulary drilling, and paired or group dialogue practice. Data were collected through participant activity observation, satisfaction questionnaires, field notes, and activity documentation, and were subsequently analyzed using descriptive qualitative techniques and simple quantitative analysis based on percentages. The results indicated that the fun learning approach fostered greater enthusiasm, participation, speaking confidence, and self-assurance among participants in using simple English expressions. The satisfaction questionnaire revealed positive responses across several aspects: easy-to-understand materials (90%), an enjoyable learning atmosphere (95%), engaging activities (93%), communicative and interactive facilitators (96%), increased self-confidence (88%), and perceived usefulness of the program (97%). Therefore, fun learning can be regarded as a relevant approach for strengthening English speaking skills among elderly learners in non-formal education settings, as it meaningfully integrates language learning, emotional support, and social interaction.